Dating the origin and diversification of Pan-Chelidae (Testudines, Pleurodira) under multiple molecular clock approaches - Holley Reguiló, Juan Alfredo (2019)
Pan-Chelidae (Testudines, Pleurodira) is a group of side-necked turtles with a currently disjointed distribution in South America and Australasia and characterized by two morphotypes: the long-necked and the short-necked chelids. Both geographic groups include both morphotypes, but different phylogenetic signals are obtained from morphological and molecular data, suggesting the monophyly of the long-necked chelids or the independent evolution of this trait in both groups. In this paper, we addressed this conflict by compiling and editing available molecular and morphological data for Pan-Chelidae, and performing phylogenetic and dating analyses over the individual and the combined datasets. Our total-evidence phylogenetic analysis recovered the clade Chelidae as monophyletic and as sister group of a clade of South American extinct chelids; furthermore Chelidae retained inside the classical molecular structure with the addition of extinct taxa in both the Australasian and the South American clades. Our dating results suggest a Middle Jurassic origin for the total clade Pan-Chelidae, an Early Cretaceous origin for Chelidae, a Late Cretaceous basal diversification of both geographic clades with the emergence of long-necked lineages, and an Eocene diversification at genera level, with the emergence of some species before the final breakup of Southern Gondwana and the remaining species after this event.